The Interaction between the Marketing Communications Audit and Visitors in Museum Facilities - Lukáč, Michal; Písař, Přemysl; Kupec, Václav; Štarchoň, Peter (Communication Today, 2021)
Museum facilities are part of an economic environment that is continually developing and subject to hypercompetitive conflicts. Museums must therefore apply adequate modern marketing tools, including marketing communications, which not only have informative and promotional functions, but at the same time enable the management of museum profitability and numbers of visitors to museums. Marketing communications for these institutions therefore represent a critical aspect of museum management. The purpose of this research study is to evaluate the levels of marketing communications to museum visitors for the purpose of acquiring feedback for museum management. At the same time, it is also possible to apply modern auditing techniques to governance and marketing communications management. This is a task undertaken by this research inquiry through experimental CASI interviews on a sample of 2,020 museum visitors over a period of four consecutive years and subsequent analyses using R statistical software. The recorded data shows a strong correlation between marketing communications and museum attendance. Based on this data, it has been possible to interactively formulate audit recommendations and a model for a marketing communications optimisation audit approach that can enable museum management to manage their marketing communications innovatively. At the same time, the results have also expanded interdisciplinary knowledge of marketing and management.